2020
DOI: 10.1590/1980-549720200011.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Uso de capacete e gravidade de lesões em motociclistas vítimas de acidentes de trânsito nas capitais brasileiras: uma análise do Viva Inquérito 2017

Abstract: RESUMO: Objetivo: Analisar o efeito do uso de capacete na gravidade de lesões em condutores e passageiros de motocicletas envolvidos em acidentes de trânsito. Métodos: Estudo de corte seccional sobre vítimas de acidentes de transporte terrestre envolvendo motociclistas, atendidos nos serviços de urgência e emergência e participantes do Inquérito de Vigilância de Violências e Acidentes (Viva Inquérito) 2017. Resultados: Verificou-se predomínio de indivíduos na faixa de 18 a 29 anos (46,6%), negros (75,2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…The rise in mortality rates of motorcyclists during this period, especially after 2000, has also been observed by other studies conducted in Brazil 13,[21][22][23] . This may well be connected to a growth in the number of motorcycles, especially in states of the Northeast region, which witnessed an increase of 1,400% in motorcycle sales between 1991 and 2008 24 .…”
Section: /10supporting
confidence: 77%
“…The rise in mortality rates of motorcyclists during this period, especially after 2000, has also been observed by other studies conducted in Brazil 13,[21][22][23] . This may well be connected to a growth in the number of motorcycles, especially in states of the Northeast region, which witnessed an increase of 1,400% in motorcycle sales between 1991 and 2008 24 .…”
Section: /10supporting
confidence: 77%
“… 10 - 12 The lack of helmet use among the young may be attributable to the fact that young individuals, in comparison to older persons, are more likely to engage in risky activities and attitudes. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Both classic and recent studies found in scientific literature report males are more subjected to trauma and injuries, mostly due to work-related practices and also because men are more likely to act impulsive and to neglect risk behaviors (Damacena et al, 2016;Souto, Corassa, Lima & Malta, 2017). Research, Society and Development, v. 10, n. 4, e43010414273, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14273…”
Section: Discussionmentioning
confidence: 99%